Measuring the complexity of military communication network based on supernetwork theory - SHI Fu-li; ZHU Yi-fan (Tongxin xuebao)
According to the structural and functional characteristics of military communication network（MCN）,through constructing the military communication supernetwork（MCSN） description model,the concept of adjacent matrix of su-pernetwork,correlation matrix of classified nodes,type assortativity coefficient,and the definitions of supernetwork mo-tif,core and the entropy of the motif were introduced.Then regarding motifs as basic construct modules of MCSN,the supernetwork motif entropy（SNME） was proposed as a complexity measure of MCN.Finally,by taking the complexity measuring steps of a naval vessels fleet communication supernetwork structure which was discussed in detail as an ex-ample,the computing results of SNME were compared with the present complexity measures,and it was demonstrated that SNME could measure the functional complexity of network when its structural complexity was determined.